Here's the question you clicked on:
Kagome_gurl8
Use the Quadratic Formula to solve the equation. –x2 – x – 5 = 0
\[–x^2 – x – 5 = 0\] 1st I would factor out -1: \[-(x^2 + x + 5) = 0\] Then divide both sides by -1 \[x^2 + x + 5 = 0\] Now I would use quadratic formula: \[x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\] a = 1, b = 1, c = 5
Oh, thank you very much :)
When in doubt, compute the discriminant to see if this is even has any real solution
b^2 - 4ac = (1)^2 - 4(1)(5) = 1 - 20 = -19 No real solution
Thats what i got also, i wanted to make sure i was doing it right. :)